Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Untuk Mengatasi Kesalahan Peserta Didik Dalam Menyelesaikan Soal Cerita Berdasarkan Prosedur Kesalahan Newman di Kelas VIII SMP Negeri 13 Padang - SULASMI . (Departemen Matematika, 2019)
This study aims to describe the types of errors and factors the cause of students making mistakes in the matter of stories, as well describe how the impact of applying the Think Talk Write (TTW) Cooperative model to the error. The types of errors are categorized according to Newman error analysis. The method used in this research is a combination of sequential explanatory model research methods. Data collection techniques this study were test and interview methods. The validity of the data is done by triangulation of techniques that compares test and interview data. Data analysis technique is done by data reduction, data presentation and data verification. The subjects in this study were students of class VIII 9 SMP Negeri 13 Padang, amounting to 31 people. The results showed that the most dominant mistake made by students was the error writing answers with a percentage of errors of 49.67%, while the smallest mistakes made by students were errors reading questions with a percentage of errors of 1.93%. Factors that cause it are students can not absorb information properly, carelessness, do not understand the material as a whole, the weak concept of prerequisites, lack of confidence in solving problems, in a hurry in solving problems and the results of incorrect answers. Based on the comparison of the results of the Pretest and Posttest after applying the Think Talk Write (TTW) cooperative learning model, it appears that the application of the learning model affects errors learners. When viewed from a comparison of the percentage of each type of error in Pretest and Posttest the results show that the percentage of each type of error has also decreased.Keywords – Student’s error, Newman Error Analysis, TTW Cooperative Mode